Thioether‐Polymer Coating for Colloidal Stabilization of Silver Nanoparticles. Issue 5 (1st March 2021) - Lutz, Johanna; Albrecht, Krystyna; Groll, Jürgen
Abstract : Enhancing the colloidal stability of silver nanoparticles (AgNPs) is crucial to maintain their unique properties allowing broad application of these NPs. Stabilization of AgNPs is usually achieved by surface modification with thiol containing polymers showing limitations owing to the nucleophilic and oxidative character, whereas chemical inert thioethers have so far received little attention. Herein, AgNPs coated with mono‐ and multivalent thiol‐ and thioether polymers are prepared to systematically investigate the adsorption kinetics onto the silver surface as well as the colloidal stability after exposure to different conditions relevant for biomedical application, such as freeze‐drying and treatment under physiological conditions. Although the thioether polymers show a slower immobilization onto AgNPs, the same or mostly even better stabilization is exhibited than for the thiol analogs. In addition, the polymer surface coverage and the polymeric arrangement of these polymers on AgNPs are calculated, as they supposedly influence the stability. Abstract : Thioether polymers are evaluated as better alternatives for functionalization of silver nanoparticle (AgNP) compared with the gold standard of coating with thiols. A systematic investigation of linear mono‐ versus multivalent thiol‐ and thioether polymers is performed in view of the colloidal stabilization efficacy after treatment in different conditions relevant for biomedical application.